Effects of different light intensities and COշ enrichment on yield and pharmaceutical quality of young ginger (Zingiber officinale roscoe) - Ghasemzadeh Daghigh, Ali (2011)
In this study, the effect of some environmental factors (light intensity and CO2 concentration) on physiological characteristics and biochemical changes of Malaysian young ginger varieties namely Halia Bentong and Halia Bara were considered. Ginger (Zingiber officinale) is herbaceous annual plant of the family Zingiberaceae, locally known as Halia in Malaysia. It is one of the most common medicinal plants used by diverse ancient cultures and has been widely used as health food and in cosmetic industries. Information on the polyphenolic compounds (flavonoids and phenolic acids) of Malaysian young ginger and their biological activities are still scarce and such data would be useful to provide information on foods containing high levels of beneficial components. A factorial experiment was designed to determine effect of different solvent polarity on extraction yield of flavonoids and phenolic acids of Malaysian young ginger varieties namely Halia Bentong and Halia Bara. The results showed extraction solvent had significant effects on total phenolics (TP), total flavonoids (TF), quercetin, catechin and rutin contents and antioxidant activity of Halia Bentong and Halia Bara. The highest content of TP (39.06mg/g dry weight), TF (7.05mg/g dry weight) and 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) assay activities (58.21%) were found in methanolic extracts compared to acetone and chloroform extracts. A factorial experiment was designed to determine effect of different light intensity (310, 460, 630 and 790µmol/m2/s) on yield and pharmeocological quality of Halia Bentong and Halia Bara. Between the two varieties and four levels of glasshouse light intensities (310, 460, 630 and 790µmol/m2/s) that were tested, Halia Bara exhibited highest TF content (8.45 mg/g dry weight) under 310µmol/m2/s, while TP was high (39.06mg/g dry weight) in this variety under a light intensity of 790µmol/m2/s. The partitioning of TF and TP at 16 weeks after planting was: leaves > rhizomes > stems. Antioxidant activities determined by the DPPH assay and ferric reducing (FRAP) activity in both varieties increased significantly with increasing TF concentration, and high antioxidant activity 62.8% for DPPH assay, and 788.5µmol Fe(II)/g dry weight for FRAP assay, were observed respectively in the leaves and rhizomes of Halia Bara grown under 310µmol/m2/s. The results of HPLC analysis indicated that synthesis and partitioning of quercetin, rutin, catechin, epicatechin and naringenin were high in plants grown under 310µmol/m2/s. The evidence from this study elucidated that the average value of flavonoids synthesis for both varieties increased (Halia Bentong 26.1%; Halia Bara 19.6%) by decreasing light intensity from 790 to 310µmol/m2/s. However, high photosynthesis rate (12.25µmolCO2/m2/s in Halia Bara), plant biomass (79.47g in Halia Bentong) and total soluble carbohydrate content (18.49 mg/g dry weight in Halia Bara) were observed at 790µmol/m2/s. A factorial experiment was designed to determine alteration of flavonoids synthesis during growth period of young ginger varieties for 16 weeks. Time to harvest was observed to be an important factor for accumulation of TF in the plants. In both varieties, the concentration of flavonoids in the leaves decreased (Halia Bentong, 42.3%; Halia Bara 36.7%), and in the rhizomes it increased (Halia Bentong 59.6%; Halia Bara 60.1%) as the growth period increased from 8 to 16 weeks. A split-split plot experiment was designed to investigate effects of two level of CO2 (400 and 800 µmol/mol) on production of primary metabolites (soluble sugar and starch), secondary metabolites (flavonoids and phenolic acids) and leaf gas exchange of Halia Bentong and Halia Bara for 16 weeks. The results showed that as CO2 levels increased from 400 to 800µmol/mol TF, TP, total soluble carbohydrates (TSC) and starch content also increased considerably. In this study, eight flavonoids and six phenolic acids were identified. In addition, after fisetin (3.11mg/g dry weight, in Halia Bara rhizome) in CO2 enriched plants, quercetin (1.33mg/g dry weight, in Halia Bara leaves), and morin (0.876mg/g dry weight, in Halia Bentong rhizome) were detected in the highest amount. Concurrently, gallic acid (0.645mg/g dry weight, in Halia Bara leaves) and vanillic acids (0.357mg/g dry weight, in Halia Bara rhizome) were the phenolic acids that were most highly detected. The most obvious finding to emerge from this study is that CO2 enriched ginger plants exhibited the ability to synthesize new compounds such as vanillic acid, cinnamic acid and salicylic acid which were not detected from gingers grown under ambient CO2 concentration. The current study is the first report of the isolation of flavonoid and phenolic compounds from Malaysian young ginger varieties and has shown these varieties are the major dietary source for flavonoids especially quercetin, fisetin and morin. Higher photosynthetic rate (10.05µmol CO2/m2/s in Halia Bara) and plant biomass (83.4 g in Halia Bentong) were observed at 800µmol/mol CO2 compare to 400µmol/mol CO2. Stomatal conductance decreased and water use efficiency increased with elevated CO2 concentration. Free radical scavenging power (DPPH) increased about 30% in Halia Bentong and 21.4% in Halia Bara by elevated CO2 concentration and the rhizomes exhibited more enhanced free radical scavenging power, with 44.9% in Halia Bentong and 46.2% in Halia Bara. In addition, enriched Halia Bara exhibited the highest anticancer activity on MCF–7 cancer cells with IC50 values of 25.3 and 27.31μg/ml respectively, for rhizome and leaf extract. The IC50 values for MDA–MB–231 exhibition were 30 and 32.81μg/ml, respectively for rhizome extract of Halia Bara and Halia Bentong. These results indicate that the yield and pharmaceutical quality of Malaysian young ginger varieties can be enhanced by controlled environment production and CO2 enrichment.